The First Eight Mitogenomes of Leaf-Mining Dactylispa Beetles (Coleoptera: Chrysomelidae: Cassidinae) Shed New Light on Subgenus Relationships - Zhang, Shengdi; Sekerka, Lukáš; Liao, Chengqing; Long, Chengpeng; Xu, Jiasheng; Dai, Xiaohua; Guo, Qingyun (Insects, 2021)
The taxonomic classification of Dactylispa, a large genus of leaf-mining beetles, is problematic because it is currently based on morphology alone. Here, the first eight mitochondrial genomes of Dactylispa species, which were used to construct the first molecular phylogenies of this genus, are reported. The lengths of the eight mitogenomes range from 17,189 bp to 20,363 bp. All of the mitochondrial genomes include 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), 2 ribosomal RNA genes (rRNAs), and 1 A + T-rich region. According to the nonsynonymous/synonymous mutation ratio (Ka/Ks) of all PCGs, the highest and the lowest evolutionary rates were found for atp8 and cox1, respectively, which is a common phenomenon among animals. According to relative synonymous codon usage, UUA(L) has the highest frequency. With two Gonophorini species as the outgroup, mitogenome-based phylogenetic trees of the eight Dactylispa species were constructed using maximum likelihood (ML) and Bayesian inference (BI) methods based on the PCGs, tRNAs, and rRNAs. Two DNA-based phylogenomic inferences and one protein-based phylogenomic inference support the delimitation of the subgenera Dactylispa s. str. and Platypriella as proposed in the system of Chen et al. (1986). However, the subgenus Triplispa is not recovered as monophyletic. The placement of Triplispa species requires further verification and testing with more species. We also found that both adult body shape and host plant relationship might explain the subgeneric relationships among Dactylispa beetles to a certain degree.
Keywords: Triplispa; phylogenetic tree; body shape; host plant; mitochondrial genome; Platypriella